INTEGRATION OF EDUCATION, SCIENTIFIC ENVIRONMENT AND PRODUCTION: METHODOLOGICAL FEATURES OF PRODUCT DEVELOPMENT IN THE STEM LABORATORY - Ramankulov, Ш.Ж.; Mussakhan, Н.П.; Bitibaeva, Ж.М.; Kurbanbekov, Б.А.; Berdi, Д. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The STEM-based laboratory is a module that combines elements of science, technology, engineering and mathematics from both a theoretical and practical point of view. In the educational process, this module examines the elements of problem-based learning to improve active learning and the learning process. In particular, teaching physics allows students to learn about digital engineering, work in educational and practical laboratories on their projects related to curricula, and improve their professional skills. This scientific study examines the methods of using the possibilities of the scientific environment and the integration of production in the development of the quality of education in physics educational programs. The purpose of this study is also to determine the impact of interdisciplinary STEM education on the labor market, factors determining the continuity of production and educational organizations. In the course of the study, multimethodic quantitative and qualitative research methods were used. A meta-analysis and systematic analysis of articles in highly regarded journals from Wos and Scopus sources was carried out. About 200 respondents participated in the quantitative data collection in the study. The STEM laboratories used the method of constructive research in order to combine physical knowledge with practice, to improve the work on the development of STEM products in scientific environments. The results of the study showed that the effective implementation of the links between the scientific environment and production in the educational process makes students competitive in the labor market. The research also revealed the technology of product development in the STEM laboratory and the methodological features of the use of products in the educational process. The results obtained correspond to global trends and have a positive impact on the development of scientific and technological trends in the country, the further development of the educational process, and the systematic formation of necessary 21st century skills among students.